Infant Mortality Based on Causes, Age, Place and Referral Case High Risk in East Sumba District - Mariana Ngundju Awang; Diyan Maria Kristin (Humanistic Network for Science and Technology (HNST), 2021)
Maternal mortality can almost certainly also mean death in infants who are conceived or born. Reportedly, 75% of babies born who lost their mothers will die before celebrating their first birthday. East Nusa Tenggara (NTT) is one of the regions with the highest infant / neonatal mortality rate in Indonesia, Infant mortality rate in East Sumba is one of the highest in East Nusa Tenggara (NTT) province and continues to fluctuate in the last five years from 2011 to 2015 and the number is 61 - 99 - 122 - 108 and 99. The research objective was to identify the cause, age, place of death of infants and referral cases in 2011 – 2015. This type of research was descriptive, cross sectional method, the total population of infant mortality cases in 2011 - 2015 was 30 cases. The sample selection used was simple random considering the time and funds as well as access to the respondent's location so that the latest infant mortality data in 2015, for which data exists, parents still remember the incident. Collection using a questionnaire for mothers / fathers / families with midwives in the village and coordinating midwives who handle ANC and case referrals. The data were processed and analyzed descriptively. The cause of infant mortality over the last 5 years in East Sumba district was 66.7% Pneumonia, as many as 46.7 percent of infants died at the age of 1 month. Based on the place of infant mortality, 80 percent of infants died at home because they were not referred and 20 percent died in PHC or Hospital for late referral. Keywords: infant mortality; risk factors; East Sumba